Saberes científicos e pedagógicos de conteúdo em biologia expressos por professores da Educação de Jovens e Adultos em Santo Antônio de Leverger – MT - Oliveira, Kalmon da Silva (2021)
This work is part of the research that seeks to understand and report the experiences of teachers when working with the discipline of Biology in High School, in the modality of Youth and Adult Education (EJA), in order to make explicit the knowledge base necessary for professional performance in the field of Natural Sciences. In this sense, the guiding question of the research is: how are the scientific and pedagogical knowledge of Biology content configured and expressed underlying the teaching of teachers in high school, when reporting the teaching they perform in Youth and Adult Education? Thus, the experiences of Biology teachers are sought in a school in Mato Grosso, directed in this process of building knowledge, with a qualitative approach based on the assumptions of Narrative Research, and using information records as questionnaires and semi-structured interviews as an instrument. The research collaborators are two professors of the discipline of Biology at the State School Dr. Hermes Rodrigues de Alcântara in the city of Santo Antônio do Leverger - MT. For data analysis, the discursive textual analysis (DTA) method is used. Therefore, it appears that the research collaborators have a good command of scientific content, demonstrate proximity and ease when teaching their teaching experiences, thus managing to transform the knowledge of the specific content making it more understandable to students. They express having harmony and rapport when reporting how area meetings are held and content decisions about the curricular knowledge to be worked on. Reports supported by the collaborators demonstrate the lack of pedagogical training on the part of the Secretariat of Education of the State of Mato Grosso. It is believed that for greater depth and reflection on the conclusion of the theme, it is pertinent to examine other factors with greater accuracy, such as: sociocultural, socioeconomic, beliefs and values.